Foam Rolling vs. Proprioceptive Neuromuscular Facilitation Stretching in the Hamstring Flexibility of Amateur Athletes: Control Trials - Pérez-Bellmunt, Albert; Casasayas-Cos, Oriol; Ragazzi, Paolo; Rodríguez-Sanz, Jacobo; Hidalgo-García, César; Canet-Vintró, Max; Caballero-Martínez, Iván; Pacheco, Laura; López-de-Celis, Carlos (International journal of environmental research and public health, 2023)
Background: the use of stretching techniques in the sports world is frequent and common thanks to their many effects. One of the main benefits of stretching is an increased range of motion (ROM). Recently, the use of a foam roller has spread in sports practice due to benefits that are similar to those of shoes observed in stretching. The objective of the following study was to compare the results of proprioceptive neuromuscular facilitation stretching (PNF) with foam rolling (FR). Methods: The design of the study was a single-blind, randomized controlled trial (clinicaltrial.gov NCT05134883), and the participants were 80 healthy young athletes. The range of motion was evaluated with a modified sit-and-reach test before, during (at 30 s), and at the end of the intervention (at 2 min). The subject’s discomfort sensation was measured using the Borg scale. Effect sizes were calculated using Cohen’s d coefficient. Volunteers were randomized into the PNF group or FR group. Results: the differences were statistically significant (p < 0.001) during the intervention in favor of PNF group. The differences at the end of intervention showed that the PNF group had a greater increase in flexibility, with this difference being statically significant (p < 0.001). The sensation of perceived exertion with PNF at the end of the intervention was similarly classified as moderate for both groups. Conclusion: Despite the fact that the use of FR is spreading in the field of sports and rehabilitation, the results of the present study suggest that the gain in flexibility in the hamstrings is greater if PNF-type stretches are used instead of FR.